The Urgency of Human Rights Approach for The Indonesian Ombudsman for combatting Discrimination - Wicaksono, Tio Tegar (Fakultas Hukum Universitas Gadjah Mada, 2024)
Abstract based on Law number 37 in the year of 2008, The ombudsman is responsible for the promotion of good governance and the prevention of maladministration within the public sector. hence, The prevailing body of research on the Indonesian Ombudsman mostly use the good governance framework to depict the Ombudsman's role in addressing instances of maladministration within the public sector. meanwhile, The role of the ombudsman primarily involves addressing a wide range of public service problems that encompass dimensions of human rights, including instances of discrimination against minority populations and vulnerable groups. Nevertheless, this aspect has been disregarded. therefore, this essay aims to address the existing gap in the literature regarding the Indonesian Ombudsman, specifically from a human rights viewpoint. This article exclusively uses the normative legal method, which involves the collection and analysis of regulations, pertinent literature, and reports from the Ombudsman. The findings indicate that the implementation of a good governance approach alone is insufficient in addressing human rights violations against disadvantaged and minority groups within public services. Similarly, the adoption of a human rights strategy is necessary to address discrimination that specifically targets vulnerable and minority populations.